(7x+2)(4x+1)(1x-5)=0

Simple and best practice solution for (7x+2)(4x+1)(1x-5)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (7x+2)(4x+1)(1x-5)=0 equation:


Simplifying
(7x + 2)(4x + 1)(1x + -5) = 0

Reorder the terms:
(2 + 7x)(4x + 1)(1x + -5) = 0

Reorder the terms:
(2 + 7x)(1 + 4x)(1x + -5) = 0

Reorder the terms:
(2 + 7x)(1 + 4x)(-5 + 1x) = 0

Multiply (2 + 7x) * (1 + 4x)
(2(1 + 4x) + 7x * (1 + 4x))(-5 + 1x) = 0
((1 * 2 + 4x * 2) + 7x * (1 + 4x))(-5 + 1x) = 0
((2 + 8x) + 7x * (1 + 4x))(-5 + 1x) = 0
(2 + 8x + (1 * 7x + 4x * 7x))(-5 + 1x) = 0
(2 + 8x + (7x + 28x2))(-5 + 1x) = 0

Combine like terms: 8x + 7x = 15x
(2 + 15x + 28x2)(-5 + 1x) = 0

Multiply (2 + 15x + 28x2) * (-5 + 1x)
(2(-5 + 1x) + 15x * (-5 + 1x) + 28x2 * (-5 + 1x)) = 0
((-5 * 2 + 1x * 2) + 15x * (-5 + 1x) + 28x2 * (-5 + 1x)) = 0
((-10 + 2x) + 15x * (-5 + 1x) + 28x2 * (-5 + 1x)) = 0
(-10 + 2x + (-5 * 15x + 1x * 15x) + 28x2 * (-5 + 1x)) = 0
(-10 + 2x + (-75x + 15x2) + 28x2 * (-5 + 1x)) = 0
(-10 + 2x + -75x + 15x2 + (-5 * 28x2 + 1x * 28x2)) = 0
(-10 + 2x + -75x + 15x2 + (-140x2 + 28x3)) = 0

Combine like terms: 2x + -75x = -73x
(-10 + -73x + 15x2 + -140x2 + 28x3) = 0

Combine like terms: 15x2 + -140x2 = -125x2
(-10 + -73x + -125x2 + 28x3) = 0

Solving
-10 + -73x + -125x2 + 28x3 = 0

Solving for variable 'x'.

The solution to this equation could not be determined.

See similar equations:

| 2/3(9x-12)=4x=6 | | 6p+5=77 | | 16x+6=360 | | 96y-154=-43y+263 | | 3/4s=2/3 | | t^2-14*t+40=0 | | 4x^3+16x^2+8x-448=0 | | 3(u+1)+2u=5(u+1)+5 | | 8z-6=24 | | .7n-4=0 | | 5x+2(3x-10)=2 | | X+4.5=11.2 | | 2x/3-7=26 | | 25/5=1*k | | -3(x+2)=1w | | 0.7n-4=.0 | | 5x+2(3x-10)=42 | | 3x+5=8x+40 | | 13g=-(9-12g)-5 | | 5x/6/180 | | -8.38v+10.71=132.382 | | 5x/6/18- | | 18/3=2*c | | 10x^2-11x=6 | | (4x)m+(5x+1)m+(5x+3)m=180 | | 5w+4(3+w)=66 | | 11.3e-10.1e+7=13.24 | | 425/68=150/x | | 53a-79=26a+29 | | 106/4=x/12 | | =x^2+10x+9 | | 5x(-1)=10 |

Equations solver categories